2017
DOI: 10.1038/s41598-017-14379-9
|View full text |Cite
|
Sign up to set email alerts
|

In situ TEM observation of alpha-particle induced annealing of radiation damage in Durango apatite

Abstract: A major issue in thermochronology and U-Th-Pb dating is the effect of radiation damage, created by α-recoils from α-decay events, on the diffusion of radiogenic elements (e.g., He and Pb) in host mineral. Up until now, thermal events have been considered as the only source of energy for the recovery of radiation-damage. However, irradiation, such as from the α-particle of the α-decay event, can itself induce damage recovery. Quantification of radiation-induced recovery caused by α-particles during α-decay even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Damage to the crystal lattice develops from self-irradiation from the natural decay of isotopes of U, Th, and Sm by ionization and electronic excitation and heavy nuclide recoil during alpha decay, as well as spontaneous fission (e.g., Weber & Matzke, 1986). This discovery is rooted in materials science approaches to characterize apatite, zircon, and titanite using X-ray diffraction, infrared and Raman spectroscopy, in situ transmission electron microscopy analysis, and hardness analysis via nanoindentation (Beirau et al, 2018;Ginster et al, 2019;Hawthorne et al, 1991;Holland & Gottfried, 1955;Li et al, 2017;Lumpkin et al, 1991;Nasdala et al, 1995Nasdala et al, , 2004Woodhead et al, 1991). Damage anneals at high temperatures and thus cumulative damage is a function of a sample's initial U, Th, and Sm content and its thermal history.…”
Section: Radiation Damage and Chemistry Controls On (U-th)/he And Ft mentioning
confidence: 99%
“…Damage to the crystal lattice develops from self-irradiation from the natural decay of isotopes of U, Th, and Sm by ionization and electronic excitation and heavy nuclide recoil during alpha decay, as well as spontaneous fission (e.g., Weber & Matzke, 1986). This discovery is rooted in materials science approaches to characterize apatite, zircon, and titanite using X-ray diffraction, infrared and Raman spectroscopy, in situ transmission electron microscopy analysis, and hardness analysis via nanoindentation (Beirau et al, 2018;Ginster et al, 2019;Hawthorne et al, 1991;Holland & Gottfried, 1955;Li et al, 2017;Lumpkin et al, 1991;Nasdala et al, 1995Nasdala et al, , 2004Woodhead et al, 1991). Damage anneals at high temperatures and thus cumulative damage is a function of a sample's initial U, Th, and Sm content and its thermal history.…”
Section: Radiation Damage and Chemistry Controls On (U-th)/he And Ft mentioning
confidence: 99%
“…In the case of monazite–(Ce), thermal annealing occurs at comparably low temperatures (Meldrum et al 1998 ). Furthermore, it has been proposed, and is discussed controversially since, as to which degree the action of alpha particles, in addition to creating Frenkel-type defects (Nasdala et al 2011 , 2013b ), may anneal alpha-recoil damage (Soulet et al 2001 ; Gautheron et al 2009 ; Deschanels et al 2014 ; Li et al 2017 ). Such alpha-assisted annealing, if relevant for a certain mineral species, might explain why actinide-bearing minerals do not accumulate radiation damage even at low temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…The latter problem may be overcome by obtaining spectra of (i) initially non-damaged minerals that were ion-irradiated in the laboratory under controlled conditions (e.g. Picot et al 2008 ; Zhang et al 2008 ; Nasdala et al 2010a , 2013b ; Deschanels et al 2014 ; Li et al 2017 ) or (ii) synthetic samples doped with short-lived alpha emitters such as 238 Pu, 241 Am or 244 Cm (e.g. Luo and Liu 2001 ; Burakov et al 2004 , 2010 , and references therein) Bregiroux et al 2007 ; Deschanels et al 2014 ; Shiryaev et al 2016 ; see also).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, understanding how the apatite structure reacts to radioactive decay over geological timescales is critical to assessing its capabilities as a potential long-term nuclear waste repository. Previous studies suggest that apatite is not as susceptible to metamictization as many other actinide-accommodating minerals, and that the energy imparted by alpha particle bombardment is sufficient to induce annealing in apatite [3,4,10].…”
Section: Apatite As a Nuclear Waste Storage Solutionmentioning
confidence: 99%
“…Previous works have used ion bombardment to simulate alpha recoil damage from actinide decay, successfully resulting in the amorphization of minerals such as zircon and apatite [8,10,37,38]. Li et al concluded that amorphous apatite will recrystallize into polycrystalline domains when exposed to alpha particle bombardment, demonstrating that the energy imparted by an incident alpha particle is sufficient to instigate annealing in apatite group minerals [10]. Because Li et al used amorphous apatite, recrystallization could form polycrystalline domains at odds with the protocrystal orientation.…”
Section: Crystallinity Of Samplesmentioning
confidence: 99%